Dynamic educational leadership teams : from mine to ours - Jennings, Matthew (Lanham, Maryland : Rowman & Littlefield, 2008)
Dynamic Educational Leadership Teams: From Mine to Ours provides school and district leaders with research-based, practical guidelines that they can use to create high-performing school and district leadership teams. High-performing leadership teams emerge with adherence to Matthew Jennings's set of simple behavioral principles, which he teaches through a sequence of interactive activities on subjects ranging from promoting productive conflict to demanding mutual and individual accountability.
I. Introduction to leadership teams -- II. Composing a leadership team -- III. Creating a common and compelling purpose -- IV. Building trust -- V. Promoting productive conflict -- VI. Establishing collective commitments -- VII. Developing mutual and individual accountability -- VIII. Focusing on collective results -- IX. Leadership team meetings.
Includes bibliographical references.
Keywords: EDUCATIONAL LEADERSHIP